Asymptotic behavior of solutions for a semibounded nonmonotone evolution equation. (14th May 2003) - Karachalios, Nikos; Stavrakakis, Nikos; Xanthopoulos, Pavlos
Abstract : We consider a nonlinear parabolic equation involving nonmonotone diffusion. Existence and uniqueness of solutions are obtained, employing methods for semibounded evolution equations. Also shown is the existence of a global attractor for the corresponding dynamical system.